Development of rapid methods of detecting pesticide residues in stored grains - Calumpang, S. M. F. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2001)
In a continuing program to expand the applicability of rapid test kits (RTKs) produced by the National Crop Protection Center, methods were developed for the fast, semi-quantitative detection of residues of 4 insecticides belonging to 3 pesticide groups, i.e., deltamethrin and cypermethrin (both pyrethroids), malathion (an organophosphate), and carbaryl (a carbamate), used in stored farm produce, i.e., mungbean (Vigna radiata), corn (Zea mays), and rice (Oryza sativa) whether whole or milled. RTKs are necessary for quick analysis of commercial farm produce which may contain pesticide residues beyond the maximum residue limits (MRLs), standards set by the FAO-WHO-supported Codex Alimentarius Commission to protect consumers all over the world.